PERLINDUNGAN HUKUM ANAK BUAH KAPAL INDONESIA PADA KAPAL PERIKANAN TAIWAN - SAFITRI, GUSRIKA; Deliana, Evi; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Opportunities for migrant workers in the field of fisheries, especially boat crews on foreign fishing vessels. Estimating that there are 36 million people involved in fishing and aquaculture activities and 15 million of them are involved in fishing. Activities in the territorial sea are basically subject to coastal state jurisdiction, while in the high seas are subject to international law. With the aim of supporting economic development and increasing national welfare, the Indonesian state has bilateral relations with Taiwan. But in the Indonesian political order it did not establish diplomatic relations with Taiwan based on the politics of One china Policy. Although it does not have diplomatic and consular relations, Indonesia's interests in Taiwan, especially economic and trade interests, are carried out by the Indonesian Economic and Trade Office. As a country subject to international law, when Indonesian citizens come to Taiwan, Taiwan must treat Indonesian citizens as well as treat their own citizens, in accordance with the standard national treatment principle. In fact, there are still many Indonesian citizens who get into trouble in Taiwan, especially Indonesian Ship Fruits working on Taiwan's Fishing Vessels, which have been explored. This problem is caused by the absence of regulations specifically regulating international standard ship crews. The destination country must balance the needs of migrant workers based on the views and needs of the country, while the sending country needs to regulate shipping policies so that the rights of migrant workers can be protected. Ship crew rights: rights to wages, rights to shelter and food, rights to care during illness / accident, rights to leave, right to transport to be repatriated. The authors suggest integrating the guidelines for the protection and safety of migrant workers from various agencies such as the ILO, IMO, and FAO and incorporating these guidelines into the national policies of each country. Indonesia pays more attention to deviations in the suitability of prospective migrant workers on foreign fishing vessels, especially Taiwan. Keywords: Legal Protection - Indonesian Vessels - Taiwan Fishing Vessels